67 Reducing Delays to Operative Management of Anti-Coagulated Patients With Hip Fractures. (6th February 2020) - Ensanullah, J; Shah, B; Fertleman, M
Abstract: Introduction: In the UK, the gold-standard treatment of a hip fracture is surgical fixation within 36 hours. Reduced delay to surgery has been shown to minimise the risk of complications. Locally, frequent delays to surgery were observed in patients taking long-term anticoagulation. There are no national guidelines regarding anticoagulation reversal and surgery timing in patients with hip fractures, and doctors are often unfamiliar with increasingly prevalent Direct Oral Anti-coagulants (DOACs). This quality improvement project aimed to reduce delays to surgery in anti-coagulated patients with hip fractures. Methods: A guideline was formulated following literature review and consultation with a Consultant Ortho-geriatrician, Orthopaedic Surgeon and Haematologist. Retrospective casenote audit was conducted including 3-month period before and after implementation. The new guideline was disseminated in poster form. Due to the observation that delays in receiving INR results resulted in reversal delay, patient's on warfarin were recommended to receive 5 mg IV Vitamin K prior to receiving INR results. The INR was rechecked after 6 hours, and if less than 1.6, surgery could proceed. Those on DOACs could undergo surgery 24 hours after the last dose providing eGFR >30, and after 48 hours if eGFR <30. Exclusions were those anti-coagulated for metallic heart valves or recent venous thromboembolism. Results: In the 3 months prior to guideline implementation, 71 patients had a hip fracture; 15 were anti-coagulated. Of these, 8 patients were delayed due to their anticoagulation. Repeat audit after implementation, included 46 patients with a hip fracture over the 3-month period; 7 were anti-coagulated. None were delayed due to anticoagulation (p < 0.05). Conclusions: This improvement project describes formulation of a simple protocol with evidence from the literature and local expert opinion in order to reduce unnecessary delays in anti-coagulated patients with hip fractures.